Barriers to inclusive education of children with autism: Ghanaian teachers' perspective - Eyram Juliet Senoo; Mabel Oti-Boadi; Efua Vivian Senoo-Dogbey; Ohenewa Josephine Bampoe; Luke Laari (Springer, 2024)
Abstract Background Autism Spectrum Disorder (ASD), a neurodevelopmental condition, has become a major concern for both developed and underdeveloped countries since the condition is associated with significant caregiver, family, and financial burdens. Approaches to educating these children, especially in their preschool years, are burdensome and demanding for both parents and teachers. Although it is recommended that children with ASD receive inclusive, age-appropriate education in mainstream school settings, there are barriers in Ghana. This study explored barriers faced by preschool teachers in implementing and adhering to inclusive education for children with ASD. Methods The study employed an exploratory descriptive qualitative design to sample 17 participants in the Greater Accra Region using a purposive sampling technique. Data was collected through an in-depth virtual interview and analyzed using content analysis. Results The study identified inadequate parental cooperation, poor ASD knowledge of the teachers, socio-cultural and political issues, and a lack of collaboration with other professionals as major barriers thwarting the success of inclusive education for children with ASD in Ghana. Conclusion These barriers affect effective and successful adherence to inclusive education for children with ASD, and as such, we recommend orientation and special training for teachers, the provision of resources for effective child inclusion, and the creation of ASD awareness during the training of pre-school teachers.